2021
DOI: 10.3390/app11083530
|View full text |Cite
|
Sign up to set email alerts
|

Strong Photoluminescence Enhancement from Bilayer Molybdenum Disulfide via the Combination of UV Irradiation and Superacid Molecular Treatment

Abstract: A direct band gap nature in semiconducting materials makes them useful for optical devices due to the strong absorption of photons and their luminescence properties. Monolayer transition metal dichalcogenides (TMDCs) have received significant attention as direct band gap semiconductors and a platform for optical applications and physics. However, bilayer or thicker layered samples exhibit an indirect band gap. Here, we propose a method that converts the indirect band gap nature of bilayer MoS2, one of the repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Research on temperature-dependent Raman spectroscopy of few-layered WS 2 provides valuable insights into their intrinsic phonon scattering processes and thermal properties [ 20 ]. Several early experiments investigated the impact of temperature on the phononic properties of few-layered TMDs, including MoS 2 , WS 2 , MoSe 2 , and others [ 21 ]. These studies have demonstrated that temperature-dependent behaviors of phononic modes in these nanosheets are attributed to the effects of thermal expansion and anharmonic resonance [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on temperature-dependent Raman spectroscopy of few-layered WS 2 provides valuable insights into their intrinsic phonon scattering processes and thermal properties [ 20 ]. Several early experiments investigated the impact of temperature on the phononic properties of few-layered TMDs, including MoS 2 , WS 2 , MoSe 2 , and others [ 21 ]. These studies have demonstrated that temperature-dependent behaviors of phononic modes in these nanosheets are attributed to the effects of thermal expansion and anharmonic resonance [ 22 ].…”
Section: Introductionmentioning
confidence: 99%